Desarrollo de un aplicativo web y móvil para el monitoreo de la crianza de animales vacunos en asociación con la hacienda Santa María ubicada en Latacunga - barrio Tandalivi. - Almachi Guachamin, Jefferson Alexander (2023)
The present technological proposal was carried out in the Santa María farm located in the Latacunga canton, Tandaliví neighborhood, whose main objective is "Develop a web and mobile application for monitoring the breeding of bovine animals", for which the adaptation of methodologies of agile practices in the project development management process, that is, certain Scrum artifacts were used together with UML unified language notations to better understand the functionality and logic of the system, at the same time research techniques were used such as the survey and the interview, good practices were used in the development process of the system coding with the PHP programming language and the CodeIgniter framework, at the same time the Android Studio tools were used together with the Java programming language applying the Mobile-D methodology to manage the development phases, thus obtaining a system in which the different life stages of cattle can be monitored, for a better representation of the results, various decision-making boards were used.